Obstetric Referrals: Scenario at A Primary Health Centre in Gujarat - Hiteshree C Patel; Birender B Singh; Mohua Moitra; S L Kantharia (Medsci Publications, 2012)
Background: Pregnancy and childbirth is associated with health risks for both the mother and child. Timely and prompt referral service has been identified as one of the effective strategies to combat related risks and adverse outcomes. In rural areas, this problem is compounded by multiple factors and referral often plays a key role to ensure favorable outcome. Objectives: Documentation of common indications & identification of constraints related to referrals in pregnancy related cases in a PHC of Gujarat. Methodology: Secondary data analysis of referral slips of referred cases from one PHC, Gujarat was done. Referral slips between 2004 and 2009 were analyzed. A total 155 pregnancy related referrals were made during this period. Results: Referral rate was 15.2%. The average age of women was 23.46±4.1 years, 12.2% women belonged to the high risk age group and 5.8% women were grand multipara. Referrals were nearly equally distributed between OPD and emergency hours highlighting the need for 24X7 services at the PHCs. Majority of referrals were during the intranatal period (64.5%), followed by antenatal cases (23.9%) and postnatal cases(11.6%). The common reasons for referral were non progressive labour (14.8%), severe anemia (10.3%), pre-eclampsia (10.3%), malpresentation (9.7%) and postpartum hemorrhage (9.7%). Out of 62.6% who required pre-referral treatment, 43.3% didn't get pre-referral treatment. Majority of pre-referral treatment were not given in intranatal period (58.9%). Conclusion: This study recommends the development of a standard referral protocol, proper training in this regard and universal adherence to this in practice.